Cohort Analysis of Consumer Expectations of Russian Population (1996–2010): Theoretical and Methodological Backgrounds - Ibragimova, Dilyara (Journal of Economic Sociology, 2014)
Consumer confidence surveys are regularly conducted in more than 50 countries, including Russia. Most of them measure how optimistic or pessimistic consumers are with respect to the economy in the near future and test the predictive power of CSI components. Only a few studies analyze the determinants of consumer expectations and examine various socio-demographic determinates of CSI components, including age. However, when assessing the effects of age one should separate age and cohort effects. The term cohort effect is used to describe the effects of being born at about the same time, exposed to the same events in the process of their socialization. The paper provides an overview of theoretical approaches and empirical research which can be used for cohort analysis of consumer expectations. The paper deals with the psychological economics of G. Katona, generation theory of K. Mannheim, N. Ryder’s conceptual approach to cohort analysis in social sciences. Special attention is given to the discussion of possible strategies to address the ”identification problem”, i. e. the linear dependency of cohort membership, age, and period. Based on consumer surveys data on saving and consumption, the paper analyzes the advantages and disadvantages of both “formal” and ‘substantive’ approaches aimed at clarifying the definitions and interpretations of age, period and cohort effects. The article raises the question of how to relate the generational and cohort analysis, as well as describing the principles of historical sociology as a methodological paradigm of such studies.